Prevalence and associated risk factors of entamoeba histolytica, E. dispar and E. moshkovskii infection among Orang Asli communities in Slim River, Perak - Syazwan Saidin (Tanjong Malim, 2020)
Prevalence and associated risk factors of entamoeba histolytica, E. dispar and E. moshkovskii infection among Orang Asli communities in Slim River, Perak by Syazwan Saidin